From Geneva to Sochi in Search of a Solution to the Syrian Problem - Neciyev, Elçin (Celal ÖNEY, 2019)
In the last months of 2010, the insurgencies in Tunisia, Egypt and Libya have gradually brought Syria undertheir influence. Years of “repressive regimes” have dasappeard in these countries. In March 2011, a similar processin Egypt, Tunisia and Libia began to be observed in Syria, and result of this, the people revolted against in regime.Despite the popular uprising, the Syrian regime has used excessive force, which has led to and still continuesa great depression throughout the country. In order to eliminate this crisis and to maintain peace in Syria, he broughtabout proxy wars between powerful states.As a matter of fact, these proxy wars have led to the emergence of two blocssupporting regime supporters and anti-regime groups in Syria. Russia, China and Iran have supported the Syrian regime, while countries such as the United States, Saudi Arabia, Turkey have supported anti-regime forces.In this study we will talk about the position of the above-mentioned regime supporters and anti-regime countries on Syria, in particular Russia’s Kofi Annan peace plan, I. Geneva meeting of the Friends of Syria, II. Geneva andIII. We will try to examine his position in the Geneva talks.

2010 yilinin son aylarinda Tunus, Misir ve Libya’da
Cenevre’den Soçi’ye “Suriye” Problemine Çözüm Arayislari
-